alemtuzumab versus interferon beta 1a for relapsing‐remitting multiple sclerosis - Zhang, Jian (Cochrane Database Syst Rev, 2017)
BACKGROUND: Alemtuzumab is a humanised monoclonal antibody that alters the circulating lymphocyte pool, causing prolonged lymphopenia, thus remoulding the immune repertoire that accompanies homeostatic lymphocyte reconstitution. It has been proved more effective than interferon (IFN) 1a for the treatment of relapsing‐remitting multiple sclerosis (RRMS). OBJECTIVES: To compare the efficacy, tolerability and safety of alemtuzumab versus interferon beta 1a in the treatment of people with RRMS to prevent disease activity. SEARCH METHODS: We searched the Cochrane Multiple Sclerosis and Rare Diseases of the CNS Group Trials Register (1 February 2017) which, among other sources, contains records from CENTRAL, MEDLINE, Embase, CINAHL, LILACS, PEDRO and the trial registry databases Clinical Trials.gov and WHO International Clinical Trials Registry Platform for all prospectively registered and ongoing trials. SELECTION CRITERIA: All double‐blind, randomised, controlled trials comparing intravenous alemtuzumab (12 mg per day or 24 mg per day on five consecutive days during the first month and on three consecutive days at months 12, 24, 36) versus subcutaneous IFN beta 1a (Rebif), 22 μg or 44 μg three times per week, or IFN beta 1a (Avonex) by intramuscular injection 30 μg once a week, in people of any gender and age with RRMS. DATA COLLECTION AND ANALYSIS: We used standard methodological procedures expected by Cochrane. MAIN RESULTS: We included three trials involving 1694 participants. All trials compared alemtuzumab 12 mg per day or 24 mg per day versus IFN beta 1a for treating RRMS. In CAMMS223, participants received either subcutaneous IFN beta 1a 44 μg three times per week or annual intravenous cycles of alemtuzumab (at a dose of 12 mg per day or 24 mg per day) for 36 months. In CARE‐MS I and CARE‐MS II, participants received subcutaneous IFN beta 1a 44 μg three times per week or annual intravenous cycles of alemtuzumab 12 mg per day for 24 months. All three studies were at risk of performance bias and attrition bias, one study was 'unclear' risk in selection bias. Compared with interferon beta 1a, alemtuzumab given at a dose of 12 mg per day probably reduces the risk of relapse (risk ratio (RR) 0.60, 95% confidence interval (CI) 0.52 to 0.70, moderate quality evidence), may reduce the risk of worsening disability (RR 0.60, 95% CI 0.45 to 0.79, low quality evidence) and the risk of developing new T2 lesions on magnetic resonance imaging (RR 0.75, 95% CI 0.61 to 0.93, low quality evidence) after 24 and 36 months' follow‐up. Mean Expanded Disability Status Scale (EDSS) scores may be similar between the treatment regimens (mean difference (MD) ‐0.35, 95% CI ‐0.73 to 0.03, low quality evidence). At a dose of 24 mg per day alemtuzumab may reduce relapse (RR 0.38, 95% CI 0.23 to 0.62, low quality evidence), worsening disability (RR 0.42, 95% CI 0.21 to 0.84, low quality evidence). The effects on EDSS scores when compared with interferon beta 1a at three years are uncertain due to the very low quality of evidence (MD ‐0.83, 95% CI ‐1.17 to ‐0.49). All three trials reported adverse events and serious adverse events. The risk of experiencing an adverse event in either alemtuzumab 12 mg or interferon groups may be similar (RR 1.03, 95% CI 0.98 to 1.08, low quality evidence). The risk of serious adverse events is probably similar between treatments (RR 1.03, 95% CI 0.82 to 1.29, moderate quality evidence). The risk of any adverse event may be similar between alemtuzumab 24 mg and interferon (RR 1.02, 95% CI 0.96 to 1.08, low quality evidence). The risk of serious adverse events is probably similar between treatments (RR 0.95, 95% CI 0.70 to 1.31, moderate quality evidence). AUTHORS' CONCLUSIONS: Annual intravenous cycles of alemtuzumab at a dose of 12 mg per day probably reduces the proportion of participants who experience relapse, may reduce the proportion of participants who experience disability worsening and development of new T2 lesions on MRI over 2 to 3 years in comparison with subcutaneous IFN beta‐1a 44 μg three times per week. Annual intravenous cycles of alemtuzumab at a dose of 24 mg per day may reduce the proportion of participants who experience relapse and disability worsening over 3 years in comparison with subcutaneous IFN beta‐1a 44 μg three times per week. An average reduction of 0.8 EDSS units with alemtuzumab compared with interferon beta‐1a was observed at a dose of 24 mg per day in one study. The rates of adverse events were similarly high for both treatments. The most frequently reported adverse events for both treatments were infusion‐associated reactions, infections and autoimmune events. The use of alemtuzumab requires careful monitoring so that potentially serious adverse events can be treated early and effectively.